Soeharto's Leadership Style and Javanese Leadership Values - Winsidi; Shabran (Neo Journal of economy and social humanities, 2025)
The New Order is always interesting to study from various perspectives, the leadership under the control of President Soeharto has a fairly long historical record, the role of the general with a friendly smile, the nickname given to Soeharto because he ran the government always spreading a smile, the Javanese leadership type became his characteristic. Here the author tries to explore the leadership style from 1966 to 1998. Soeharto's political journey is an important concern, especially his policies which are often controversial towards the interests of Muslims, many policies are considered not in accordance with the wishes of Muslims such as not being allowed by clerics to be involved in politics because they are considered to be a stumbling block in the politics of the New Order led by Soeharto. Soeharto's policy in the final phase of his leadership saw a change in policy, many political policies were very pro-Islamic groups, teachers throughout Indonesia and providing Umrah and Hajj, not only that, Soeharto also established a thousand mosques throughout Indonesia, of course this policy was very well received by the Islamic religious group which is the majority religion in Indonesia, the aroma of Islamic politics was excited again, there were no more policies that conflicted with Islam, regardless of the political pressure at the end of Soeharto's leadership, this was evidence that he heard and realized that what he had been doing did not get the support of Islamic politics because it was considered contrary to the political policies that have been planted so far.